Analysis of the Most Influential Factors on Customer Satisfaction - Wulansari, Retno; Octovia , Carina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This paper seeks to determine factors which more influenced to customer satisfaction at PT Pantara Wisata Jaya Seribu Islands Resort? These factors were price, and service quality. Researcher have a tested to price on customer satisfaction partially, and service quality on customer satisfaction partially, including price and services quality on customer satisfaction simultaneously. Methodology/approach – This research used associative quantitative methods by using SPSS 26 to process the research data. The sample collection technique used simple random sampling technique. The sample was calculated by using the Slovin formula where 92 respondents were selected.Findings –The results of simultaneous test (f- test) of price and service quality have a significant influence on customer satisfaction. Service quality factor more influenced on customer satisfaction as per t-test resulted. Researcher found that 45% of independent variables price and service quality on customer satisfaction , and 55% was influenced by other variables which not examined. Novelty/value – As customer satisfaction has been an important factor in resort business, especially for Indonesia to increase economic growth, it is vital to understand how to maintain customer satisfaction in resort business.